A CONCEPTUAL FRAMEWORK TO REINVIGORATE THE HANDLOOMS SECTOR IN INDIA: MODELLING THROUGH ARTIFICIAL INTELLIGENCE METHODS LEVERAGING SYSTEMS THINKING APPROACHES - Kone, Venkata Satyanarayana (Digital Repository of Theses, 2023)
This exploratory inquiry intends to uncover and comprehend the problems of the languished handloom industry and impoverished artisans. Further, the study suggests conceptual frameworks for the revival of the Indian Handloom Sector. Handloom craft is a lasting legacy of great imagination, artistry and aesthetics practised as far back as 4000 BC in India. Until the late 18th century, India was a global hub of exquisite textiles and accounted for over 50% of the worldwide supply. The sector currently faces headwinds and grapples with multifarious problems, such as low productivity, disrupted supply chain, restricted credit flow, weak marketing, inadequate infrastructure and obsolete technology, among others. Moreover, with the incongruity of government policies and declining support and protection, the handloom industry is further impaired by the predatory competition from powerlooms. The study adopted mixed methods of data collection and multiple data analytical methods. The quantitative data gleaned from over 11,000 weaver households and a few vi personal interviews for qualitative insights in the Prakasam district of Andhra Pradesh, India, constituted a big dataset. The study conceived four models based on disparate influencing factors identified within the three perspectives; productivity and supply chain, human capital, and policy and implementation. Data were analysed wielding Artificial Intelligence and Machine Learning tools. The results were then scanned and explicated, employing Systems Thinking and Sustainable Livelihoods Approaches for accentuating the interrelations, patterns and trends. This study revealed a complex web of activities and interactions that resulted in the industry's downswing and consequent marginalisation of weavers. The study provided significant evidence about how the neglect of economic, social, and policy perspectives engendered structural distortions in the artisanal socioeconomic landscape. The study established the adverse effects of degraded human capital, eroded productivity factors, and disrupted supply chains. The study further disclosed that the government's claim of support to handlooms is more vaunted than the field-level reality. This paper provided policymakers and executives with policy and implementation frameworks to address the gaps and inconsistencies. The dissertation finally suggests long-term investment in human capital, technology and infrastructure associated with sustainable policies and schemes for bolstering productivity and competitiveness.